(untitled) (Plant Tissue Culture and Biotechnology, 2022)
The developed Anaerobic/Intermittent aerobic-Magnetic Activated Sludge (AI-MAS) process was found suitable for the continuous removal of phosphorus, nitrogen and organic compounds simultaneously from wastewater. This AI-MAS process reactor consisted of a small anaerobic compartment (first stage) placed at the corner of the intermittent aeration tank (second stage) with a magnetic separator in the middle. Better sludge separation was observed at 1-6 rpm of the magnetic drum. Using AI-MAS process, continuous removal of about 90% T-P, 96% T-N and 94% soluble CODCr were achieved with the loading rate of 3.5 mg/l T-P, 16 mg/l T-N and 250 mg/l CODCr, for the period of 160 d at the rate of 6 hrs hydraulic retention time (HRT). Simultaneous removal of phosphorus and nitrogen from the wastewater was possible due to coexistence of both phosphorus and nitrogen removal bacteria within the same sludge biomass. Phosphorus removal was performed through phosphate accumulation in aerobic condition and released again in anaerobic condition with the concomitant uptake of organic substances. Nitrification and denitrification occurred simultaneously in non-aeration/aeration (NA/A) cycle of the intermittent aeration. Plant Tissue Cult. & Biotech. 32(1): 21-29, 2022 (June)